2006
DOI: 10.1074/jbc.m509959200
|View full text |Cite
|
Sign up to set email alerts
|

Guide Molecule-driven Stereospecific Degradation of α-Methylpolyamines by Polyamine Oxidase

Abstract: FAD-dependent polyamine oxidase (PAO; EC 1.5.3.11) is one of the key enzymes in the catabolism of polyamines spermidine and spermine. The natural substrates for the enzyme are N 1 -acetylspermidine, N 1 -acetylspermine, and N 1 ,N 12 -diacetylspermine. Here we report that PAO, which normally metabolizes achiral substrates, oxidized (R)-isomer of 1-amino-8-acetamido-5-azanonane and N 1 -acetylspermidine as efficiently while (S)-1-amino-8-acetamido-5-azanonane was a much less preferred substrate. It has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…We recently reported that mammalian polyamine oxidase, normally using achiral substrates, displays cryptic stereospecificity when ␣-methylated polyamines are used as the substrates (32,33). In fact, the latter results (33) indicate that polyamine oxidase has a k cat /K m value (efficiency of the enzyme catalysis) for the (S,S)-isomer of Me 2 Spm that is nearly 30 times higher than that for the (R,R)-isomer. However, this difference may not be practically relevant as non-acetylated polyamines are poor substrates for mammalian polyamine oxidase in the absence of aldehydes.…”
Section: Tablementioning
confidence: 90%
“…We recently reported that mammalian polyamine oxidase, normally using achiral substrates, displays cryptic stereospecificity when ␣-methylated polyamines are used as the substrates (32,33). In fact, the latter results (33) indicate that polyamine oxidase has a k cat /K m value (efficiency of the enzyme catalysis) for the (S,S)-isomer of Me 2 Spm that is nearly 30 times higher than that for the (R,R)-isomer. However, this difference may not be practically relevant as non-acetylated polyamines are poor substrates for mammalian polyamine oxidase in the absence of aldehydes.…”
Section: Tablementioning
confidence: 90%
“…Similarly, SPD was a major metabolite with APAO, but some other competing pathways were also detected. Interestingly, with charge retaining EtSPM and DESPM the reaction velocity is slower when compared with N 1 -AcSPM and N 1 ,N 12 -DiAcSPM, respectively (Järvinen et al 2006a). BnSPM was metabolized to SPD by both oxidases, APAO being more efficient than SMO.…”
Section: Discussionmentioning
confidence: 99%
“…SMO (PAOh1) was initially cloned and characterized in 2001 (Wang et al 2001). Cloning of both the enzymes has made them readily available for recombinant protein production that has facilitated further testing of their substrate properties (Järvinen et al 2006a; Wang et al 2003; Wang et al 2005a). During polyamine catabolism, SPM and SPD are first acetylated by spermidine/spermine N 1 -acetyltransferase (SSAT) and subsequently oxidized by APAO to produce SPD and PUT, respectively, and to yield stoichiometric amounts of hydrogen peroxide and 3-acetamidopropanal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies, in which (S)- and (R)- isomers of α-methylspermidine and (S,S)-, (R,S)-, and (R,R)-diastereomers of α,α′-(dimethyl)spermine have been used, have confirmed and extended these important findings (67, 191196). Such studies have shown the maintenance of nucleic acid structure (196, 197), the stereospecificity of oxidation reactions (192, 194), the ability of derivatives that can support hypusine synthesis to support growth (67, 188, 190), and the role of polyamines in other growth processes including hair synthesis (198), liver regeneration, and adipocyte differentiation (199). Of particular interest is the ability to overcome acute liver damage and pancreatitis related to polyamine depletion by provision of α-methylspermidine or α,α′-(dimethyl)spermine (168, 193, 195, 200, 201).…”
Section: Polyamine Analogs and Derivatives As Research Tools And mentioning
confidence: 99%